Metal-based catalysts for persulfate and peroxymonosulfate activation in heterogeneous ways: A review - Zheng, Xiaoxian; Niu, Xiaojun; Zhang, Dongqing; Lv, Mengyu; Ye, Xingyao; Ma, Jinling; Lin, Zhang; Fu, Mingli (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Heterogeneous metal-catalysts for oxidants activation were presented.•The activation mechanisms involved in catalysts/oxidants system were elucidated.•The prospects and strategies for the sustainable application were proposed. A growing number of emerging organic contaminants associated with the potential risks for ecosystem and human health are frequently detected in environment. Sulfate radical-based advanced oxidation processes have attracted increasing attention during the past decades, owing to their high reactivity and oxidation capability of a wide range of toxic and non-biodegradable organic compounds. Metal-based materials have been proven to be effective heterogeneous catalysts for activating persulfate to degrade many refractory organic pollutants. This article reviews the up-to-date research progresses on various heterogeneous metal-based catalysts for persulfate (PS) and peroxymonosulfate (PMS) activation, including single metal and mixed metal catalysts. The activation mechanisms of these catalysts and their fundamental behaviors in PS/PMS activation are emphatically elucidated, in which contaminants can be eliminated through radical and/or non-radical reaction pathways. In addition, an in-depth discussion about metal composite namely metal spinel, metallic glasses and other metal hybrids in PS or PMS systems for organic degradation and possible environmental applications are presented. Finally, the perspectives on the metal-based PS/PMS activation method and their remediation potential for recalcitrant compounds in practical application are also proposed.